Aerobic exercise increases connexin43 expression in rat cardiac muscle - Fransisca Chondro; Minarma Siagian; Dewi IS Santoso (Faculty of Medicine, Universitas Trisakti, 2013)
Background Intercellular communication in cardiac muscle is effected by connexin, particularly connexin43 (Cx43), forming gap junctions in cardiomyocytes. Aerobic physical exercise may result in increased left ventricular size and function. The purpose of the present study was to assess the effect of aerobics and detraining on C43 expression and distribution in rats.MethodsThis was an in vivo experimental study on 32 young male Wistar rats. The animals were divided into the following 8 groups and their interventions: I : 4 weeks of aerobics (A4); II: exercise control for 4 weeks (C4); III: 4 weeks of aerobics plus 4 weeks of detraining (A4D4); IV: 8-week control (C8); V: 12 weeks of aerobics (A12); VI: 12-week control (C12); VII: 12 weeks of aerobics plus 4 weeks of detraining (A12D4); VIII: 16-week control (C16). Rat cardiac tissue was subjected to immunohistochemical assay to determine total Cx43, intercalated disc Cx43, and lateral Cx43. Independent t-test was used to compare all Cx43 parameters between control and treatment groups. ResultsAfter aerobics, there were significant differences in total Cx43, intercalated disc Cx43, lateral Cx43, and intercalated disc Cx43 and lateral Cx43 percentages between control and treatment groups (p<0.05). Between-group comparison in treatment groups did not find significant differences between exercise-only groups and groups with exercise plus detraining. Cx43 surface area tended to decrease after detraining. ConclusionsAerobics significantly increases Cx43 levels in rat hearts. Detraining decreases intercalated disc Cx43 and lateral Cx43.